Validation of the Questionnaire for the Structured Assessment of the Use of Complementary Medicine Methods and Procedures in Patients from the S3 Guideline Complementary Medicine in Oncology and Practical Use of it in Patients with Gynecological Cancer - Seitz, Katharina; Theuser, Anna-Katharin; Hack, Carolin C.; Fasching, Peter A.; Emons, Julius; Brückner, Lena; Au, Katharina; Beckmann, Matthias W.; Beierlein, Milena (Geburtshilfe und Frauenheilkunde, 2025)
For the first time, an S3 guideline on complementary medicine in oncology was published in 2021, 2024 in May version 2.0 was published. The broad spectrum of complementary and integrative medicine was presented at the highest level of evidence, the respective established interventions were comprehensively addressed, and recommendations were made in the case of sufficient data availability. The guideline also contains a questionnaire for a risk-adapted evaluation of utilized CIM (complementary and integrative medicine) interventions. In this article, the clinical validation of this questionnaire from the guideline is carried out, as well as a descriptive analysis of utilization of CIM interventions in a cohort with gynecologial cancer.The present study is a cross-sectional study conducted at the Women’s Hospital of the University Hospital Erlangen. In a first stage, rolled out from January to February 2022, fifty patients completed the questionnaire for the structured assessment of the use of complementary medicine from the S3 guideline “Complementary Medicine in Oncology”, as well as a validation questionnaire. The latter included the comprehensibility of the questions, the time taken to complete them, as well as any problems encountered and suggestions for improvement. After successful validation of the questionnaire, in the second phase, patients with gynecologic cancer were invited to participate in the survey.The patient population was characterized by descriptive analyses of age, educational level, lifestyle factors such as dietary habits and physical activity, as well as tumor characteristics and treatment. In addition, the frequency of complaints and the utilization of complementary interventions and procedures, classified according to their risk of interactions, were analyzed.Validation showed that forty-five out of fifty (90%) patients felt that the questionnaire was clear to understand. Forty-seven (94%) of respondents indicated that the time taken to answer the questions was reasonable. In figures, 42% needed less than five minutes and 48% less than ten minutes.When looking at the utilization of CIM in patients with gynecological tumors, most participants were suffering from ovarian cancer (n = 61, 41.8%), followed by endometrial cancer (n = 33, 22.6%), cervical cancer (n = 32, 21.9%) and vulvar cancer (n = 20, 13.7%). In total, the utilization of a CIM intervention was described 267 times. According to the traffic light classification system in the guideline questionnaire the interventions of the green category (low risk for interaction) (n = 124, 46.4%) was the most commonly used. Therapies in the yellow category were used slightly less frequently (n = 93, 34.8%). CIM interventions of the red category were mentioned 50 times (18.7%).To date, there has been a lack of standardized surveys that explicitly include CIM.The questionnaire published in the S3 guideline is well understandable and concise. It can therefore be used in a structured way not only in research, but also in everyday clinical practice to avoid interactions and increase patients’ safety. However, further training of oncologists is required regarding the application of the interventions mentioned in the questionnaire.
Keywords: cancer; gynecological oncology; complementary medicine; integrative medicine